The Influence of Implementing Problem-Based E-Modules on Students' Motivation And Learning Outcomes on Colloid Systems Chemistry Materials in Senior High School - Nainggolan, Fedora Deroly Br; Nainggolan, Bajoka (UNDIKMA, 2024)
The research aims to determine the effect of implementing problem-based e-Modules on student motivation and learning outcomes in colloid system material in class XI SMA Negeri 9 Medan. This research method is descriptive quantitative with taking samples from the population by random sampling as many as 60 students as samples (30 students in class XI-2 as experiments and 30 students in class XI-1 as controls). Data was collected through tests and questionnaires, then analyzed using SPSS 24 for Windows with a one-party t-test. The results of the analysis show that students' chemistry learning motivation increased significantly with the implementation of the e-Module, with the average score of the experimental class (71.33%) being higher than the control class (49.00%). This is supported by the results of the one-party t-test which shows a significance value of 0.001 < 0.05. Apart from that, there is a significant influence on students' chemistry learning outcomes, with the experimental class post-test score (79.67) being higher than the control class (74.5) and the one-tailed t-test significance value of 0.031 < 0.05 . Research also shows a positive correlation between motivation and student learning outcomes with a sig value of 0.026 < 0.05, confirming that the application of problem-based e-Modules contributes to improving student chemistry learning outcomes in colloidal systems material.